The many manifestations of a single disease: neuroborreliosis. Issue 1 (2nd January 2021) - Zulfiqar, Sajida; Qureshi, Anum; Dande, Ranadheer; Puri, Chahat; Persaud, Kia; Awasthi, Shankar
ABSTRACT: Lyme disease is a tick-borne illness that occurs in stages, multiple organs and tissue with highly variable clinical presentation. Most commonly, it presents with seventh cranial nerve palsy, often mimicking stroke and atypical rash (erythema migrans). Atypical presentations include abdominal pain, ileus/pseudo-obstruction and constipation thought to be due to autonomic dysfunction. Other less common presentations include Syndrome of Inappropriate Antidiuretic Hormones (SIADH). Lyme disease should be a differential when a patient presents from Lyme endemic areas with abdominal pain, constipation and SIADH in the setting of other causes of gastrointestinal and renal symptoms ruled out. Here we present a case of multisystem involvement in a single patient with Lyme Disease along with neuroborreliosis (neurological manifestation of Lyme disease).